2015
DOI: 10.1186/s12978-015-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported postpartum morbidity: prevalence and determinants among women in Marrakesh, Morocco

Abstract: BackgroundMaternal mortality is a public health problem particularly in developing countries. This is mainly related to maternal morbidity, especially during the post-partum period (Haemorrhage, infections…). In Morocco, little is known about maternal morbidity within the population. The aim of this study is to determine the prevalence of self-reported postpartum morbidity and grasp its determinants.MethodsThis descriptive and analytic cross-sectional survey was carried out in six health centers drawn randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…This nding has been con rmed by other studies conducted in developing countries [13,14]. As a result, children (especially daughters) are considered as a source of help for the elderly, which may prevent or at least delay their movement to health care facilities [15]. This data corroborates the ndings of many earlier studies [6,10].…”
Section: Socio-demographic and Economic Characteristicssupporting
confidence: 89%
“…This nding has been con rmed by other studies conducted in developing countries [13,14]. As a result, children (especially daughters) are considered as a source of help for the elderly, which may prevent or at least delay their movement to health care facilities [15]. This data corroborates the ndings of many earlier studies [6,10].…”
Section: Socio-demographic and Economic Characteristicssupporting
confidence: 89%
“…These findings contradict with findings presented in a study that was conducted by Siveregi (2019) that reported increased chances of complications in those that utilise TM as compared to those that do not cite higher chances of suffering from complications such as hyper uterine stimulus [ 25 ]. This argument is also bolstered by Elkhoudri (2016) in their study that reports that utilisation of traditional medicines presents huge risks for the mother and the baby [ 26 ]. Furthermore, studies suggest that due to the lack of regulated doses, usage of TM can lead to hyper uterine stimulus and other complications [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the women interviewed in Morocco were illiterate or had a low level of education. Although many studies in Morocco have shown an association between maternal morbidity and education, [ 24 , 25 ], it appears that the latter is not the most predominant factor in women’s lack of knowledge of HDP. In another context, You et al [ 23 ] argue in their study that women, regardless of literacy level, have a poor understanding of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%